Clinical features of pure hereditary spastic paraplegia - Qian-qian WEI; Xiao-yan GUO; Wei SONG; Ke CHEN; Bei CAO; Hui-fang SHANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2013)
Objective To study the clinical features and diagnostic methods of patients with pure hereditary spastic paraplegia (HSP). Methods Patients diagnosed with pure HSP from October 2006 to February 2013 admitted to Department of Neurology, West China Hospital, Sichuan University were included. The patients were assessed by the Spastic Paraplegia Rating Scale and the clinical features were reviewed. Results Thirty-three HSP patients (21 men and 12 women) were included in the study. Thirteen patients (39.39%) had family history of HSP and the most common genetic mode of the familial cases were autosomal dominant inheritance (11/13). The mean age of onset were (20.35 ± 15.55) years and the mean disease duration were (12.77 ± 9.83) years. All of the included patients presented with signs of impairment of the pyramidal tract such as increased muscular tone, tendon hyperreflexia and positive Babinski's sign of the lower limbs. Impairment of the pyramidal tract also presented in the upper limbs in some patients. Scissors gait appeared in 29 patients and feet deformity in 5 patients. Atrophy of thoracic cord on MRI were presented in 5 patients while 2 patients complicated with peripheral nerve damage. Four patients had a novel exon 10-17 deletion in SPG4 gene. There were no differences in onset age, disease duration and mean score of the Spastic Paraplegia Rating Scale between male and female patients as well as between patients with and without family history (P > 0.05, for all). Conclusion The onset age of pure HSP is variational and males are more common than females. The most common inheritance mode is autosomal dominant and most of the cases are characterized by impairment of the pyramidal tract of the lower limbs and occasionally bladder dysfunction and peripheral nerve damage. Gender and family history do not affect the clinical features. Clinical features, family history and spinal cord MRI will assist the correct diagnosis, and making a definite diagnosis needs genetic tests.